Implementasi Nilai-Nilai Pancasila Dalam Pembelajaran Ramah Anak Untuk Membentuk Karakter Anak Usia Dini 4-5 Tahun - Suadah; Dewi Pusparini; Musayyadah (Institut Agama Islam Negeri Madura, 2024)
Pancasila values are the basis for citizen of Indonesian behavior. Therefore, implementing Pancasila values ​​must be done from an early age. The background of this research is the problem of implementing Pancasila values based on child-friendly learning to form character for 4-5 years old at RA Sirojul Ulum, Pangtonggal Village, Proppo District, Pamekasan Regency. The purpose of this research is to find out what Pancasila values ​​based on child-friendly learning are developed at RA Sirojul Ulum, how Pancasila values based on child-friendly leaarning ​​to form character are implemented at RA Sirojul Ulum, also obstacles in implementing Pancasila values ​​and exertion to overcome them. This type of this research used descriptive qualitative. The data collection techniques used in this research are observation, interviews and documentation. The sources of the data include primary data secondary data. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The results of the research show that the learning system based on child-friendly learning at RA Sirojul Ulum has several Pancasila values ​​implemented, however in providing learning that adheres to Pancasila values ​​for early childhood is not optimal, so not all Pancasila values ​​are implemented. The application of Pancasila values ​​is also poorly understood because there is no learning about Pancasila values ​​which are directly related to daily life.